Room temperature magneto optic exchange springs in DyFe2/YFe2 superlattices - Wang, D; Morrison, C; Buckingham, A; Bowden, G; Ward, R; de Groot, P (2009)
Exchange springs in hard-soft DyFe2 / YFe2 superlattices at room temperature, studied by the magneto optic Kerr effect, are presented and discussed. The measured hysteresis loops clearly show the formation of exchange springs. Deviations from the previously established 1 / ts2 law for the bending field on the soft layer thickness is observed. This is attributed to (i) the reduced anisotropy of the hard layer, and (ii) the presence of anisotropy in the soft layer, at room temperature. A one dimensional model of exchange coupled spins is employed to understand the observed behavior. This involves solving the Landau-Lifshitz-Gilbert equations. Good agreement is found between the experimental and simulated results. © 2008 Elsevier B.V. All rights reserved.